Lack of prognostic significance of neuroendocrine differentiation and stem cell antigen co-expression in resected early-stage non-small cell lung cancer - Gottschling, Sandra; Jensen, Katrin; Herth, Felix; Thomas, Michael; Schnabel, Philipp Albert; Herpel, Esther (Anticancer research, 2013)
Background: Neuroendocrine (NE) carcinomas of the lung exhibit expression of various stem cell antigens, and except for carcinoid tumours, carry a poor prognosis. Despite the fact that 10%-30% of all non-small cell lung carcinomas (NSCLC) which are not classified as NE carcinomas also show expression of NE markers, data on their prognostic significance are conflicting and analyses of the expression and relevance of stem cell antigens in this subgroup are lacking. Materials and Methods: Tissue specimens of 100 resected early-stage NSCLC were analyzed by immunohistochemistry for the expression and prognostic significance of NE markers. Moreover, the subgroup of NSCLC with NE differentiation (ND) were assessed for the expression and prognostic significance of the stem cell antigens CD117, CD133 and breast cancer resistance protein-1 (ABCG2). Results: ND correlated significantly with adenocarcinoma histology (p=0.035), but not with prognosis. In the subgroup of ND-NSCLC (n=80), the stem cell antigens CD117, CD133 and ABCG2 were expressed in 51%, 14% and 33% of the cases, but likewise, showed no association with prognosis or clinicopathological characteristics. Conclusion: This study indicates that neither ND, nor co-expression of the stem cell antigens CD117, CD133 or ABCG2, have a prognostic significance in resected early-stage NSCLC.
Gesehen am 24.02.2020